Catechin Contents, Antioxidant, and Antibacterial Activities of Different Types of Indonesian Tea (Camellia sinensis) - Nuryana, Isa; Ratnakomala, Shanti; Fahrurrozi, Fahrurrozi; Juanssilfero, Ario Betha; Andriani, Ade; Putra, Filemon Jalu Nusantara; Rezamela, Erdiansyah; Wulansari, Restu; Prawira-Atmaja, M. Iqbal; Lisdiyanti, Puspita (Annales Bogorienses, 2020)
Tea is one of the most popular beverages in the world. Produced from Camellia sinensis leaves, tea has been studied to provide health benefits due to the content of important metabolites. This study aimed to investigate the catechin contents, antioxidant, and antibacterial activities of Indonesian tea varieties, namely green tea, black tea, and white tea. Tea infusion was prepared by extracting 1 g of each sample into 10 mL of distilled water and incubated at 80 °C for 60 min. The catechin and epigallocatechin gallate (EGCG) contents of tea extracts were determined using high-performance liquid chromatography (HPLC). Antioxidant activity was measured using the free radical method with 2,2-diphenyl-1-pycrylhidrazyl (DPPH), while antimicrobial activity was assesed using paper disc diffusion assay. The results indicated that green tea had the highest contents of catechin (646 ± 17.14 mg/L) and EGCG (997.8 ± 36.72 mg/L), and antioxidant activity with IC50 of 5.65 µg/mL. Furthermore, green tea and white tea extracts showed inhibitory activity against Gram-positive bacteria such as Micrococcus luteus, Bacillus subtilis, and Staphylococcus aureus whereas black tea had no activity against all bacterial strains tested. Generally, we concluded that white tea and green tea contributed to the higher content of catechins and exhibited strong antioxidant and antibacterial properties.